Given the function f(x)=-2x^2+4x-7, find f(-4)
2 answers:
Let's begin by evaluating f(x) using the value of 3: f(x) = 2x2 - 4x - 4 (original function) f(3) = 2(3)2 - 4(3) - 4 (plugging in 3 for x) f(3) = 2 (computed result) Now let's evaluate g(x) using the value of 3: g(x) = 4x - 7 (original function) g(x) = 4(3) - 7 (plugging in 3 for x) g(x) = 5 (computed result) Finally, we'll sum our results: (f + g)(3) = 2 + 3 (add f(3) and g(3)) <span>(f + g)(3) = 5 (final answer)</span>
Please see picture attached.
You might be interested in
Answer:
Hold on a sec i cant remember
<em>3,2</em>
Step-by-step explanation:
Reflection across the x-axis:
(x,y) -> (x,-y)
In other words, you want to <u>change the sign of the y</u>.
(3,-2) -> (3,2)
The answer is 30, assuming it is a cube,
<em>Answer</em>
= 11
<em>Explanation</em>
f(x) = x² + 3x- 7
To get the value of f(x) when x = 3, we substitute x with 3 in the function f(x).
f(x) = x² + 3x- 7
= 3² + (3×3) -7
= 9 + 9 - 7
= 11
Answer:
2:5
Step-by-step explanation: